Community-level environmental characteristics predictive of childhood stunting in Bangladesh - a study based on the repeated cross-sectional surveys - Khan, Jahidur Rahman; Hossain; Awand, Nabil (Taylor & Francis, 2022)
This article was published in The International Journal of Environmental Health Research [ © 2020 Rights managed by Taylor & Francis)] and the definite version is available at: https://doi.org/10.1080/09603123.2020.1777947 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/09603123.2020.1777947